2019
DOI: 10.1038/s41541-019-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

An oral alpha-galactosylceramide adjuvanted Helicobacter pylori vaccine induces protective IL-1R- and IL-17R-dependent Th1 responses

Abstract: Helicobacter pylori causes chronic gastric infection that can lead to peptic ulcers and is an identified risk factor for gastric cancer development. Although much effort has been put into the development of a Helicobacter pylori vaccine over the last three decades, none has yet reached clinical application. Specific challenges pertaining to effective H. pylori vaccine development include the lack of proven vaccine-effective antigens and safe mucosal adjuvants to enhance local immune responses as well as the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
(67 reference statements)
0
25
0
1
Order By: Relevance
“…Some potential antigen proteins, including OMP and recombinant fusion protein, require plasmid transfection (Voland et al, 2003;Liu et al, 2011). Alpha-galactosylceramide (α-GalCer), an oral adjuvant, was synthesized in a series of reactions (Longet et al, 2019). In order to stimulate OMV production to obtain adequate yields, various stress factors such as temperature, and nutrient depletion or overdosing are controlled and administered during cultivation, which is technically challenging (Klimentova and Stulik, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some potential antigen proteins, including OMP and recombinant fusion protein, require plasmid transfection (Voland et al, 2003;Liu et al, 2011). Alpha-galactosylceramide (α-GalCer), an oral adjuvant, was synthesized in a series of reactions (Longet et al, 2019). In order to stimulate OMV production to obtain adequate yields, various stress factors such as temperature, and nutrient depletion or overdosing are controlled and administered during cultivation, which is technically challenging (Klimentova and Stulik, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvants, namely immunomodulators, are small molecules that enhance the immunogenicity of vaccines to improve pathogen suppression and reduce the vaccine dose. While classical adjuvants, such as potassium alum, have been frequently used, subsequent studies have generated novel candidates (Arzeno Carranza, 1950;Sjokvist Ottsjo et al, 2013;Liu et al, 2017;Longet et al, 2019). For anti-H. pylori vaccines, cholera toxin (CT) and Escherichia coli heat-labile enterotoxin (LT) are widely used as adjuvants to boost the efficacy of mucosal vaccines in mice (Lehours and Ferrero, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vaccine formulation elicited strong intestinal and systemic Th1 responses as well as significant antigen‐specific mucosal and systemic antibody responses. They also reported that the protective intestinal Th1 responses induced were dependent on CD1d, IL‐1R as well as IL‐17R signaling 39 . Therefore, α‐GalCer could be a promising adjuvant for inclusion in an oral vaccine.…”
Section: Vaccinesmentioning
confidence: 98%
“…Some iNKT cell agonists have been investigated as adjuvants to enhance immune responses in immunotherapy and vaccination strategies [86]. Lavelle and colleagues demonstrated the potential of the iNKT cell activator α-Galactosylceramide (α-GalCer) as an oral adjuvant to enhance intestinal immune responses induced by experimental whole-cell killed ETEC [87], Vibrio cholerae [88] and Helicobacter pylori [89] antigens in mouse models. In addition, a novel oral delivery-integrated system named Single Multiple Pill ® (SmPill ® ), containing oil-in-water emulsions formulated as 1 mm minispheres, was reported to effectively protect and enhance the release of various drugs in targeted intestinal regions [90].…”
Section: Oral (Gastrointestinal) Vaccinesmentioning
confidence: 99%